Students' Perceptions on E-Learning Use in Fourth and Sixth Semesters of English Department in UMPO - Ana Maghfiroh; Risqi Ekanti Ayuningtyas Palupi; Galuh Erlina Putri (TLEMC (Teaching and Learning English in Multicultural Contexts), 2020)
This research is qualitative descriptive research with the subject are the fourth and sixth semesters of the English Department at the Muhammadiyah University of Ponorogo (UMPO). Semesters four and six each consist of 16 students. So the total number of respondents was 32 students. The data collections were questionnaires, observation, and interviews to find out student's perception of E-learning use, E-learning element, and the impact of students in E-learning use. The results of the study show that according to students' perception E-learning is effectively carried out in lectures because with E-learning, students can access lecture material wherever and whenever. Besides, by using E-learning, the learning resources and learning activities of students are also diverse because E-learning is equipped with attractive features. One of the E-learning platforms used by English Department lecturers at Muhammadiyah University in Ponorogo (UMPO) is Bebas UMPO (MOODLE), Google Classroom, Edmodo, and Whatsapp. There are some standard features from applications/platforms that used by lecturer: Features from Bebas UMPO are "Forums", "Quizzes", "SCORM packages", "Resources", and "Assignments"; feature from Google classroom is "Classwork"; part from Edmodo are "Chatting," and "Quiz" and feature from Whatsapp is "Group chat". The result of the study is students more active in responding during lecture activities using E-learning. Keywords: Students' perception, E-learning